Pengujian Bacillus spp dan pseudomonad fluoresen dalam Mengendalikan Penyakit Layu Bakteri Nilam Secara in planta di Rumah Kaca - Chrisnawati Chrisnawati (Fakultas Pertanian Universitas Tamansiswa Padang, 2011)
The study of controlling bacterial wilt disease on patchouli plant (Rasltonia solanaceraum) in Laboratory and Green house of KP Balittro Laing Solok from Mart to Juny 2006. The aims of the study were to find out the effective combination form product of Bacillus spp and Fluorescent pseudomonad. Isolate of Bacillus sp. and Fluorescent pseudomonad in separation and combination as treatments were isolated from the rhizosphere of healthy patchouli plant, and selected based on antagonistic activity against Ralstonia solanacearum screening in vitro, for three months. Further isolates of Bacillus spp. and fluorescent pseudomonads best of the test results are taken for testing the combination in the same way with the previous test. Treatment was arranged in a completely randomized design (CRD) with six replications. The assessment parameters were incubation period of symptoms disease and disease intensity. The results showed that Bacillus sp. Bc26; Bc80 and Bc81 and Fluorescent pseudomonad Pf101; Pf146 and Pf170 could control the bacterial wilt disease better than the others. In addition, the combina-tion of Bacillus spp (Bc26; Bc80; Bc81) and Fluorescent pseudomonad (Pf101; Pf146; Pf170) could control the bacterial wilt disease better than separately. The combination of Bacillus sp. Bc26 with Fluorescent pseudomonad Pf101; Bc26 with Pf 146; and Bc80 with Pf101 could control the bacterial wilt disease better than other combinations that delayed the incubation period of symptom disease from 14 to 50-55 DAI and decreased the disease intensity of bacterial wilt from 69,6 to 4,2-9,9%. The results of the experiment showed that Bacillus sp. Bc26 and Fluorescent pseudomonad Pf101, Pf146 and Pf147 isolates have the highest activity on controlling the bacterial wilt disease either in combination or separation.